A comparative study of typical early celadon shards from Eastern Zhou and Eastern Han dynasty (China). (October 2020) - Yan, Lingtong; Liu, Miao; Sun, Heyang; Li, Li; Feng, Xiangqian
Highlights: Comparison of the proto and mature Chinese celadon in different aspects. The bodies of early Zhejiang celadon have many similarities. The samples of different groups differ in the appearance of the glaze. Abstract: Many Chinese scholars thought that the development of celadon could be divided into two stages, proto and mature. The two types of wares were considered to have significant differences in product quality. In recent years, people have many controversies about the celadon classification, because many proto shards with high quality from Eastern Zhou dynasty (770–221 BCE) were unearthed. In this paper, we collected these typical proto celadon shards and some early mature wares from Eastern Han Dynasty (24–220 CE), and compared them in terms of body, glaze and firing. Based on analysis results, we believe that both types of potshards used porcelain-stone as the raw material and were applied lime-rich glaze. Most of them have relatively high firing temperature (above 1000 °C) and completed mineralogical transformation in their fired bodies. The differences between them are mainly glazes' appearance and thickness uniformity, content of minerals (especially cristobalite) contained in the bodies and control of firing process. These conclusions should be useful for the further discussion about the celadon classification.